2024
DOI: 10.1021/acs.inorgchem.3c04498
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Creation of Surface Defects on Pd@NiPd with Core–shell Hierarchical Structure Toward Boosting Electrocatalytic Activity

Chen She,
Shihuan Hong,
Ning Song
et al.

Abstract: A deep insight into surface structural evolution of the catalyst is a challenging issue to reveal the structure–activity relationship. In this contribution, based on a surface alloying strategy, the dual-functional Pd@NiPd catalyst with a unique core–shell hierarchical structure is developed through selective crystal growth, surface cocrystallization, directional self-assembly, and reduction process. The surface defects are created in situ on the outer NiPd alloy layer in the electrochemical redox processes, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…After analysis of the Pd 3d XPS spectrum of the PdCo/COFs-1 catalyst (Figure B), It can be observed that Pd exists in two various species, Pd(0) and Pd n + . In the XPS spectrum of Pd 3d 5/2 , the corresponding peaks at 335.4 and 337.5 eV are ascribed to Pd(0) and Pd n + species. , It is found that Pd is mainly with the chemical state of zerovalent Pd(0), and some Pd is also present with oxidized Pd (Pd n + ) in PdCo/COFs-1. The existence of Pd n + may be assigned to highly dispersed Pd atoms in COFs, which are easily oxidized after prolonged exposure in air .…”
Section: Resultsmentioning
confidence: 92%
“…After analysis of the Pd 3d XPS spectrum of the PdCo/COFs-1 catalyst (Figure B), It can be observed that Pd exists in two various species, Pd(0) and Pd n + . In the XPS spectrum of Pd 3d 5/2 , the corresponding peaks at 335.4 and 337.5 eV are ascribed to Pd(0) and Pd n + species. , It is found that Pd is mainly with the chemical state of zerovalent Pd(0), and some Pd is also present with oxidized Pd (Pd n + ) in PdCo/COFs-1. The existence of Pd n + may be assigned to highly dispersed Pd atoms in COFs, which are easily oxidized after prolonged exposure in air .…”
Section: Resultsmentioning
confidence: 92%